Influence of Classroom Environment, Teacher Support, and Student Motivation on Academic Performance - Asghar, Mumtaz; Naeem, Iram; Shehbaz, Iqra (Kashmir Journal of Academic Research and Development, 2026)
The academic achievement is still one of the most important predictors of the educational effectiveness, and the clarification of the factors that can shape the academic performance of students has become one of the central concerns of the educational research. This paper has analyzed the impact of classroom setting, teacher encouragement, and student motivation on academic performance amongst students. The quantitative research design was used, and data were measured using a structured questionnaire which was given to undergraduate students in six universities in Lahore, Pakistan (three public and three private institutions). One hundred and fifty-six valid responses were used. The research adopted descriptive statistics, reliability test based on the use of Cronbach alpha and correlation analysis and Structural Equation Modeling (SEM) to test the hypothesized relationship among the variables. The findings showed that classroom atmosphere, teacher support and student motivation had strong positive impacts on academic performance. Out of these variables, student motivation was found to have the greatest impact on academic achievements, then teacher support and classroom environment. The results show the value of establishing a favorable learning climate, enhancing the teacher-student relationships, and encouraging the student motivation to handle academic performance. The research offers useful information to the teachers, university administrators, and policymakers in developing effective strategies that can help students to learn better and achieve improved grades.
Keywords: Classroom Environment; Teacher Support; Student Motivation; academic performance; Higher Education; Structural Equation Modelling